Representación pictórica con estilo realista tomando como motivo la labor artesanal en las ladrilleras del Cantón Catamayo, Loja-Ecuador - Tillaguango Reyes, Kelly Joselyn (2023)
The present research work entitled " Representación pictórica con estilo realista tomando como motivo la labor artesanal en las ladrilleras del cantón Catamayo, Loja- Ecuador " proposes the analysis of the artistic movement of realism, starting from a theoretical study of the basis of thought, technical and aesthetic characteristics, and artistic references of Realism, to generate a plastic proposal based on the theme of artisanal work in the brick factories of Catamayo, with the purpose of paying tribute to the identity of said canton, through painting. To achieve the objectives, different research methods were implemented, including deductive and inductive methods, to review philosophical and aesthetic currents and concepts of Realism. An on-site study and artist book recording were also conducted to collect direct information on the artisanal work of bricks, to subsequently support the plastic proposal. The experimental method was used to employ pictorial techniques and plastic elements such as frames, paints, and other artistic production materials. Being a practical work, the production of artistic works is divided into phases: pre-production, production, and post-production, where it starts from the preparation of sketches, the execution of works, and the dissemination of the same, through different physical and/or virtual exhibition spaces. Keywords: Realism in art, artistic works, craftsmanship, brick kilns in the Catamayo canton